Islamic Religiosity, Corporate Governance, and Sustainability Performance: A Systematic Literature Review - Ahmad Rio Lubis; Besse Mardiah Sari; Dyah Mayasari; Edwar Kusumayadi; Rustam Hanafi (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to synthesize the development of research on the relationship among Islamic religiosity, corporate governance, and sustainability performance through a systematic literature review approach. This topic is important because sustainability in sharia-based entities cannot be explained solely through formal governance mechanisms, such as the board of commissioners, audit committee, board of directors, or Shariah Supervisory Board; it must also be understood through moral values, Islamic ethics, and spiritual accountability. This study applies a PRISMA-based SLR approach by selecting articles from Scopus and Sinta databases. From 105 initial articles, 30 relevant articles were selected for analysis. The findings show that Islamic religiosity functions as an informal control mechanism that encourages trustworthiness, honesty, justice, and responsibility in business decision-making. Corporate governance serves as a formal mechanism to supervise and direct organizations toward greater transparency, accountability, and sustainability orientation. However, the literature also indicates that the influence of Islamic corporate governance on sustainability performance is not always consistent. This suggests that sharia governance should not stop at administrative compliance; it must be directed toward substantive governance oriented to maqasid al-Shariah. This study contributes theoretically by integrating Agency Theory, Stakeholder Theory, Legitimacy Theory, Institutional Theory, and Maqasid al-Shariah in explaining sustainability accountability in sharia-based entities.